KONSEP SOSIOLOGIS DALAM PENDIDIKAN PERSPEKTIF IBN KHALDUN: SUATU ANALISIS PSIKOPEDAGOGIK - Mulasi, Syibran; Walidin, Warul; Silahuddin, Silahuddin; Syibran Mulasi (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2023)
Education and social development are things that are mutually integrated and provide mutually beneficial effects. Ibn Khaldun is one of the figures who dared to create an excellent design for social science in the Middle Ages. This discussion aims to discover Ibn Khaldun's concept of education in social development. This study uses a qualitative approach with a type of literature study. Data was collected by exploring historical texts and research results related to social and educational concepts from the Khalduniyan perspective. The results of the study found that social relations that begin with the term "Ashabiyah" have had a positive effect on the success of education in society, as the view is that the goal of society is to pass on culture to the next generation, so it needs to be equipped with the concept of "ashabiyah" which can help create it. a social group that is strong and able to preserve and pass on cultural values ​​to future generations, based on these ashabiyah relationships, education will be better formulated because these bonds of solidarity help give birth to peace and create cohesion between fellow tribes and communities and ashabiyah relationships which can have a negative impact on the quality of education in society.